2021
DOI: 10.1002/app.50547
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of chitosan/kefiran electrospun nanofibers for tissue engineering applications

Abstract: Chitosan (CS)-based nanofibrous scaffolds are very promising in tissue engineering applications. However, electrospinning of CS is not possible unless using toxic solvents such as trifluoroacetic acid or by blending with other polymers. In the present study, we investigated CS-based nanofibers' fabrication by blending it with kefiran as a natural polysaccharide. A series of solutions with various CS to kefiran ratios were prepared and underwent electrospinning. The effects of main process parameters, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…A co‐pigmentation effect of lactic acid formed during fermentation on anthocyanins in BCJ was therefore investigated in this study and this anthocyanin stabilizing and/or color‐enhancement effect was revealed for the first time. Moreover, possible effects of exopolysaccharides such as kefiran, glucan, and cycloamylose on color and antioxidant activity of FBs were also discussed for the first time in the light of the data obtained from our study and previous studies in the literature 9‐13 …”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…A co‐pigmentation effect of lactic acid formed during fermentation on anthocyanins in BCJ was therefore investigated in this study and this anthocyanin stabilizing and/or color‐enhancement effect was revealed for the first time. Moreover, possible effects of exopolysaccharides such as kefiran, glucan, and cycloamylose on color and antioxidant activity of FBs were also discussed for the first time in the light of the data obtained from our study and previous studies in the literature 9‐13 …”
Section: Introductionmentioning
confidence: 53%
“…This edible exopolysaccharide, which is a water‐soluble branched glucogalactan including d ‐glucose and d ‐galactose, also exhibits antioxidant activity as well as antibacterial, antitumor, anti‐inflammatory, and biocidal activity 9 . The maximum kefiran production by mixed kefir grain microflora occurred at pH 5.6, 3.9, and 3.6 10 . All these results revealed that the reason for the highest antioxidant activity in the FB at pH 3.90 could have been attributable to the kefiran or other exopolysaccharides produced by mixed kefir grain microflora.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofibers are an important class of materials used in various fields such as filtration, tissue engineering, protective suits, energy storage, etc. [ 5 , 6 ]. Although electrospinning is one of the most used methods to produce nanofibers, its commercial use is limited due to its low production speed and appropriateness of a limited number of materials.…”
Section: Introductionmentioning
confidence: 99%
“…35 The blending process is not only easy to be conducted, but also can be facilely to tailor components and compositions of the composite nanofibers for functional applications. [36][37][38] What is more, this simple process hold the largest promise for preparation on an industrial scale. In this experiment, PLA/sulfadiazine sodium/proteinase K nanofibers were prepared based on the single-fluid emulsion electrospinning technology.…”
Section: Introductionmentioning
confidence: 99%